Implementasi Metode Regresi Linear Sederhana Untuk Prediksi Harga Cabai Rawit - Moha Lalapa, Nazarullah; Warid; Serwin (Jurnal Ilmiah Ilmu Komputer Banthayo Lo Komputer, 2023)
Abstract ; The potential for developing cayenne pepper farming is widely open, especially in Gorontalo Province. After being designated as the second leading commodity in Gorontalo province after corn, the total cayenne pepper production in 2020 reached 147,292 tons (Central Bureau of Statistics of Gorontalo Province in 2020). Gorontalo District is one of the centers for cayenne pepper production in Gorontalo Province. The production contribution until 2020 reaches 35.65% of the whole cayenne pepper production in Gorontalo Province. This contribution places Gorontalo District as the second-largest producer of cayenne pepper after Bone Bolango. The high price of cayenne pepper production in Gorontalo District often causes a market price to drop by up to IDR 20,000/kg, while in fact, it is before religious holidays.  The cayenne pepper price soars drastically. To cope with the problem, it is necessary to use a prediction technique using the Simple Linear Regression and MAPE method. This research aims to design a system to predict the price of cayenne pepper. The variables used are Production as the value of X and Price as the value of Y. Based on the prediction results, it gains an error rate of 24.00% or an accuracy rate of 76.00%.  It means that the system designed is feasible to be used or applied to predict the price of cayenne pepper. Keywords: simple linear regression, mape, cayenne pepper